Pre-deployment Year Mental Health Diagnoses and Treatment in Deployed Army Women - Wooten, Nikki R. (Adm Policy Ment Health, 2017)
We estimated the prevalence of select mental health diagnoses (MHDX) and mental health treatment (MHT), and identified characteristics associated with MHT during the pre-deployment year (365 days before deployment) in active duty Army women (N = 14,633) who returned from Iraq or Afghanistan deployments in FY2010. Pre-deployment year prevalence estimates were: 26.2 % for any select MHDX and 18.1 % for any MHT. Army women who had physical injuries since FY2002 or any behavioral health treatment between FY2002 and the pre-deployment year had increased odds of pre-deployment year MHT. During the pre-deployment year, a substantial percentage of Army women had MHDX and at least one MHT encounter or stay. Future research should determine if pre-deployment MHDX among Army women reflect vulnerability to future MHDX, or if pre-deployment MHT results in protection from chronic symptoms.